1985
DOI: 10.1159/000176986
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Cardiac Arrhythmia: Effects of Lipids on Age-Related Changes in Myocardial Function in the Rat

Abstract: Male rats were fed for 3–4 months (short-term) or 12–15 months (long-term) on a standard laboratory diet alone (control) or supplemented with sunflower seed oil (SSO, 12 % w/w) or sheep kidney fat (SKF, 12% w/w). Papillary muscles were electrically driven (1 Hz, 5 ms, supramaximal voltage) at 37 °C in Krebs-Henseleit solution, and contractions were measured isometrically. Both the positive inotropic responses to CA++ and the incidence of spontaneous tachyarrhythmias under catecholamine stress were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 25 publications
7
35
0
1
Order By: Relevance
“…The lower food consumption in hypercaloric diet rats than controls equalled out caloric intake between the three groups, which resulted in similar final body weights. These data agree with previous experiments using UFA or SFA rich diets [8][9][10][13][14][15] . Analysis of relationships between ventricle weights and rat final body weights showed that animals submitted to SFA diets had biventricular hypertrophy compared to controls, and RV hypertrophy compared to UF animals.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The lower food consumption in hypercaloric diet rats than controls equalled out caloric intake between the three groups, which resulted in similar final body weights. These data agree with previous experiments using UFA or SFA rich diets [8][9][10][13][14][15] . Analysis of relationships between ventricle weights and rat final body weights showed that animals submitted to SFA diets had biventricular hypertrophy compared to controls, and RV hypertrophy compared to UF animals.…”
Section: Discussionsupporting
confidence: 93%
“…Although previous studies have shown that diet caused depressed cardiac function depression in isolated rabbit 12 and rat 13 papillary muscle, recent data from our laboratory 15 have shown that, in agreement with other authors 7,9,11,14 , UFA diet does not alter functional performance. On the other hand, there are few reports on the relationship between SFA rich diets and cardiac function.…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations